Analysis On Students’ Speaking Skills Through Automotive Youtube Video As Self Study Media - Wati, Bela Mustika; Suhartono, Luwandi; Sumarni (Kirana Publisher (KNPub), 2025)
Automotive youtube video refers to the study of self-propelled automobiles or machines that applies to standard automobiles, sports cars, tractor- trailers, marine automobiles motorcycles, and more. In the millennial era, students not only use youtube to watch but also to enhance their speaking skills. Youtube can be a media for students to study by themselves. Self- study is focuses on the individual's own practice and role in it, as well as exploring deeper to understand motivations, beliefs, and concerns about a specific part of practice. This descriptive qualitative study conducted to find how the implementation of Automotive Youtube video in developing students’ speaking skills. The population of this study was 15 Mechanical Engineering students at 12th grade of SMK Negeri 7 Pontianak as the sample. The instrument used in this study is observation, questionnaire, and interview. Based on the result, students implementations on automotive youtube video wasdifferent each other. This result showed that students have distinctive ways in implementing automotive youtube video as self-study media. It will be useful for the teacher to make learning English better related to their interests.